Post-harvest losses in rural-urban value chains: Evidence from Ethiopia - Minten, Bart; Tamru, Seneshaw; Reardon, Thomas (International Food Policy Research Institute, 2019)
We study post-harvest losses (PHL) in important and rapidly growing rural-urban value chains in Ethiopia. We analyze self-reported PHL from different value chain agents – farmers, wholesale traders, processors, and retailers – based on unique large-scale data sets for two major commercial commodities, the storable staple teff and the perishable liquid milk. PHL in the most prevalent value chain pathways for teff and milk amount to between 2.2 and 3.3 percent and 2.1 and 4.3 percent of total produced quantities, respectively. We complement these findings with primary data from urban food retailers for more than 4,000 commodities. Estimates of PHL from this research overall are found to be significantly lower than is commonly assumed. We further find that the emerging modern retail sector in Ethiopia is characterized by half the level of PHL than are observed in the traditional retail sector. This is likely due to more stringent quality requirements at procurement, sales of more packaged – and therefore better protected – commodities, and better refrigeration, storage, and sales facilities. The further expected expansion of modern retail in these settings should likely lead to a lowering of PHL in food value chains, at least at the retail level.